Genetic variation of the Mudskipper (Periophthalmus argentilineatus) in the mangrove ecosystem, North Coast of Aceh, Aceh Province, Indonesia - IRMA DEWIYANTI; PUTRI KHAIRANI AMALIA SIREGAR; CHITRA OCTAVINA; NURFADILLAH NURFADILLAH; NURFADLI NURFADLI; KASI MARIMUTHU (Society for Indonesian Biodiversity, 2025)
Abstract. Dewiyanti I, Siregar PKA, Octavina C, Nurfadillah, Nurfadli, Marimuthu K. 2025. Genetic variation of the Mudskipper (Periophthalmus argentilineatus) in the mangrove ecosystem, North Coast of Aceh, Aceh Province, Indonesia. Biodiversitas 26: 6399-6409. Mudskipper (Periophthalmus argentilineatus), a species belonging to the Gobiidae family of the Perciformes order, is an important ecological indicator of mangrove health, yet information on its genetic diversity in Aceh remains limited. This study analyzes genetic variation in mudskipper populations from the northern coast of Aceh using mitochondrial Cytochrome Oxidase Subunit I (COI) gene sequencing. Although the species has been widely studied in other regions of Indonesia, no molecular genetic baseline has ever been reported for Aceh populations, creating a critical gap in understanding their genetic structure and conservation status. Twenty samples were collected in Aceh Besar and Banda Aceh populations and combined with 19 additional COI sequences obtained from GenBank. The results showed that the mudskipper species in the research locations were P. argentilineatus. In addition, P. argentilineatus populations from Aceh Besar and Banda Aceh showed no detectable genetic variation, as reflected by low genetic distance values indicating close genetic relatedness. This pattern suggests that similar environmental pressure may be contributing to genetic homogeneity between the two populations. However, genetic variation of P. argentilineatus was moderate in the Bali population, and there was a high genetic distance between the Aceh Besar and Bali populations, as well as Banda Aceh and Bali (0.393). These findings highlight the need for conservation strategies that maintain mangrove habitat integrity and promote connectivity among regional mudskipper populations. Maintaining mangrove habitat connectivity and implementing periodic genomic monitoring are critical future steps to preserve gene flow in P. argentilineatus populations along the North Coast of Aceh.